Prevalence of Underweight: A Matter of Concern among Adolescents in Osun State, Nigeria - Funke, Olumakaiye Motunrayo (Pakistan Journal of Nutrition, 2008)
Prevalence of undernutrition among adolescents in developing world has shown a decline during the last decade. Adolescents make up approximately 20% of the world`s population. There is a dearth of research on adolescent nutrition in developing countries. The aim of this cross sectional study was to determine the prevalence of undernutrition, overweight and obesity as measured by Body Mass Index (BMI) in a representative sample of adolescents aged 10-19 years in Osun State of Nigeria. Adolescents (n = 401) from 32 schools in urban and rural districts of the state responded to a sociodemographic questionnaire. Body mass index for age was calculated and the prevalence of underweight, overweight and obesity was determined based on WHO/NCHS value of